An Open-Label, Randomized Field Trial Demonstrates Safety and Immunogenicity of Inactivated gE-Deleted Marker Vaccine Against Infectious Bovine Rhinotracheitis in Cattle - Bhaskar Ganguly; Sarvesh Tayshete; Deepa Padinjare Melepat; Sudhakar Awandkar; Srinivas Karnati; Priyabrata Pattnaik; Anand Kumar Kanakasapapathy (Vaccines)
Background: Infectious Bovine Rhinotracheitis (IBR), Infectious Pustular Balanoposthitis (IPB), Infectious Pustular Vulvovaginitis (IPV), late-term abortions, and neurological and systemic disease are common manifestations of Bovine Herpesvirus-1 (BoHV-1) infections. IBR is enzootic to India and several other countries across the world. Globally, both live attenuated and inactivated vaccines are available commercially for the control of the disease. This communication reports the results of an open-label, randomized field trial of an inactivated IBR marker vaccine in cattle. Methods: An indigenously developed, inactivated, glycoprotein-E (gE)-deleted marker vaccine was subjected to a field trial involving 90 healthy cattle of more than three months of age, evaluating its safety and immunogenicity. Results: Vaccination was safe without any adverse and serious adverse events, except a self-limiting and self-subsiding induration at the site of injection in a few cases. The vaccine caused elevation of body temperature but within normal physiological range; no derangements in feed intake or milk yield were recorded. A total of 90% of the subjects developed protective titers of SNT50 ≥ 8 after receiving both doses of initial vaccination and maintained protective titers until 180 days thereafter. Conclusions: Altogether, our findings uphold that the indigenously developed, inactivated gE-deleted marker vaccine against IBR is safe and results in protective levels of immunity for at least six months in cattle of more than three months of age.